1969
DOI: 10.1063/1.1671720
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Isolation Study of the Infrared and Ultraviolet Spectra of the Free Radical HCO. The Hydrocarbon Flame Bands

Abstract: The photoproduction of H or D atoms from a variety of sources in a carbon monoxide matrix or in an argon matrix to which a small concentration of carbon monoxide has been added leads to the appearance of prominent ultraviolet absorptions between 2100 and 2600 Å, all of which may be assigned to HCO or DCO. Both the CO-stretching and the bending vibrational modes are appreciably excited in the transition. Evidence is presented indicating that the transition observed in the matrix experiments is the same one resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(69 citation statements)
references
References 12 publications
10
59
0
Order By: Relevance
“…After a short photolysis time (150 s), the ice exhibits weak absorptions at 1861 and 1090 cm −1 . These mid-IR absorption bands were previously assigned to the HCO · radical by Milligan & Jacox (1969). This observation is consistent with experiments performed by Bouwman et al (2010b), where the electronic HCO · signature is found in the 500 to 660 nm spectral range.…”
Section: Ionization Efficiency In Co Icesupporting
confidence: 80%
“…After a short photolysis time (150 s), the ice exhibits weak absorptions at 1861 and 1090 cm −1 . These mid-IR absorption bands were previously assigned to the HCO · radical by Milligan & Jacox (1969). This observation is consistent with experiments performed by Bouwman et al (2010b), where the electronic HCO · signature is found in the 500 to 660 nm spectral range.…”
Section: Ionization Efficiency In Co Icesupporting
confidence: 80%
“…[5,7] Infrared absorptions for C 4 H 2 , the CCH radical, cation and anion are common to laser-ablated metal and acetylene experiments. [46][47][48][49] A weak HCO band [50] appears at 1862 cm À1 on annealing and it attests the formation of H atoms for the fa- vorable reaction with trace CO impurity present in all of these experiments. In addition weak absorptions at 1972, 1908, and 1760 cm À1 are near the IR-silent fundamental of C 2 H 2 , 13 C 2 H 2 , and C 2 D 2 , and these bands are due to acetylene clusters in the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…With our photon fluence the corresponding photodissociation cross-section can be estimated to be σ photo = 7.8 × 10 −19 cm −2 which is ten times lower than the value measured in the case of pure formaldehyde. New features grow at 2342, 2138, and 1860 cm −1 (Table 5) that can be readily assigned to CO 2 , CO, and HCO, respectively (Gerakines et al 1996;Milligan & Jacox 1969). In addition to these three products already observed in the case of the photolysis of pure formaldehyde, a broad feature is also detected in the C−O stretching region around 1100 cm −1 (Fig.…”
Section: Vuv Photolysis Of Pure H 2 Co Solid Filmmentioning
confidence: 86%
“…The small band at 1846 cm −1 is attributed to solid HCO radical (Milligan & Jacox 1969;Hudson et al 2005). In our experimental conditions, HCO is the only radical species that can be safely assigned.…”
Section: Vuv Photolysis Of Pure H 2 Co Solid Filmmentioning
confidence: 99%